Prevalence and correlates of depression and anxiety symptoms among older adults in Shenzhen, China: a cross-sectional population-based study - Jianhong Wang; Xiaodong Peng; Liqin You; Shan Jin; Shengming Zhang; Wenxuan Hu (BMJ Open, 2024)
Objectives To investigate the prevalence of depression and anxiety symptoms among older adults in an urban district in China, as well as their associated factors.Design Cross-sectional study.Setting General communities in Shenzhen, Guangdong, China.Participants A total of 5372 community-dwelling older adults aged 65 years or older were initially recruited. Ultimately, 5331 participants met the inclusion criteria and were included in this study.Methods Participants completed a sociodemographic questionnaire, along with assessments including the Patient Health Questionnaire-9, Generalised Anxiety Scale-7, UCLA Loneliness Simplification Scale, Insomnia Severity Index Scale (ISI), Community Dementia Brief Screening Scale and the 8-item Dementia Screening Questionnaire. Statistical analyses included the Shapiro-Wilk test, independent t-test, Wilcoxon rank test, χ2 test and univariate and multivariate linear regression analysis.Results The prevalence of depression and anxiety symptoms among older adults in Shenzhen communities was 10.4% and 11.3%, respectively. In multivariate analysis, age (B=−0.01, p<0.05), relatively poor health status in the past year (B=1.00, p<0.01), poor health status in the past year (B=2.40, p<0.01), ISI score (B=0.21, p<0.01), -item Ascertain Dementia Questionnaire (AD8) score (B=0.22, p<0.01), UCLA Loneliness Scale (ULS) score (B=0.24, p<0.01) were significantly associated with the severity of depression symptom, Compared with their respective reference categories, relatively poor health status in the past year (B=0.50, p<0.01), poor health status in the past year (B=1.32, p<0.01), ISI score (B=0.23, p<0.01), sleep duration (B=0.05, p<0.01), AD8 score (B=0.21, p<0.01), Community Screening Instrument for Dementia score (B=0.13, p<0.01), ULS score (B=0.22, p<0.01) were significantly associated with the severity of anxiety symptom.Conclusions We observed a high prevalence of depression and anxiety symptoms among older adults in this study. The existing welfare system and infrastructure should remain and targeted mental health programmes addressing the identified risk factors should be proposed.